Young Activists’ Communicative Practices of Resilience: The Challenge of Disinformation Toward the 2024 European Elections - D’Ambrosi, Lucia; Parito, Mariaeugenia; Pasciuto, Fabrizia (PARTECIPAZIONE E CONFLITTO, 2026)
This article presents findings from a qualitative study on the communicative practices of young Italian activists during the lead-up to the 2024 European elections. Specifically, the study examines the phenomenon of disinformation and its potential to disrupt the electoral campaign, highlighting the active participation of civil society in the political process and their ability to navigate disinformation can significantly influence the strength and resilience of Europe. Semi-structured interviews were conducted with members of youth organizations, both informal and institutionalized. The results show that highly educated and civically engaged young people use digital tools and hybrid media ecosystems to promote critical, transnational debates. Resilience emerges as a relational capacity rooted in the socio-political context, where youth activism develops alternative discursive spaces to counter democratic erosion. A key insight is the educational role assumed by these activists: in response to perceived institutional shortcomings, they act as informal educators, informing and mobilizing peers. This role contributes to reinforcing democratic values and fostering a more resilient European public sphere.